Fluoride Ion as Ligand and Hydrogen Bond Acceptor: Crystal Structures of Two Dinuclear CuII Complexes Built on a Diazecine Template - Olguín, Juan; Bernès, Sylvain; Gasque, Laura (2012)
Two dinuclear CuII complexes based on a diazecine ligand were characterized by X-ray diffraction, one of which includes the rare CuII–F bond, resulting from dissociation of a BF4 − ion. The F− ligands actively participate in the crystal structure, behaving as acceptors for hydrogen bonding.